2008
DOI: 10.1039/b714219f
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative molecular analysis with molecular bands emission using laser-induced breakdown spectroscopy and chemometrics

Abstract: The present work describes the first quantitative molecular prediction using laser-induced molecular bands along with chemometrics. In addition, this spectroscopic procedure has demonstrated the first complete quantitative analysis utilizing traditionally insensitive elements for pharmaceutical formulations. Atomic LIBS requires certain sensitive elements, such as Cl, F, Br, S and P, in order to quantitate a specific organic compound in a complex matrix. Molecular LIBS has been demonstrated to be the first suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…In Baudelet et al [62] it is shown that molecular emission in femtosecond plasmas is greater than in plasma obtained by nanosecond irradiation. Doucet et al [63] combined chemometrics with intensity of molecular emission in LIBS to measure the composition of pharmaceutical formulations. The authors used standards to calibrate their method and no information was provided on the relative proportion of atoms and molecules in the plasma.…”
Section: Failure Of Stoichiometric Compositionmentioning
confidence: 99%
“…In Baudelet et al [62] it is shown that molecular emission in femtosecond plasmas is greater than in plasma obtained by nanosecond irradiation. Doucet et al [63] combined chemometrics with intensity of molecular emission in LIBS to measure the composition of pharmaceutical formulations. The authors used standards to calibrate their method and no information was provided on the relative proportion of atoms and molecules in the plasma.…”
Section: Failure Of Stoichiometric Compositionmentioning
confidence: 99%
“…Quantitative methods employing multivariate calibration, such as those based on partial least squares regression (PLSR) [4][5][6][7]10,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], principal component regression (PCR) [7,32,33,41,43,44], multi-linear regression (MLR) [32] or artificial neural networks (ANN) [30,45,46] have been found. PLSR applications were used to predict the main elemental composition [36,37] and characterization [38] of samples of the jewelry industry and its application to study the matrix effects in steel samples [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…During the LIBS measurement process, the plasma spectrum contains spectral characteristics of atom, iron, and molecule fragments, but we only used the atomic spectral line in this study. For certain specific measurements, the spectral characteristics of molecular fragments can be observed and used to directly image the molecular distributions [41,46,47,48]. Theoretically, LIBS can measure nearly all elements, but it is a problem for elements that exist in air, e.g., C, H, and O.…”
Section: Discussionmentioning
confidence: 99%